Association of IDH1 Mutations with Epilepsies in Patients with Diffuse Adult Glioma according to the WHO 2021 Classification - Džurlić, Almir; Omerhodžić, Ibrahim; Rovčanin, Bekir; Alagić, Faruk; Ahmetspahić, Adi; Zahirović, Salko; Mehmedika-Suljic, Enra (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Tumors of the central nervous system comprise a wide range of over 100 histological distinct subtypes with different descriptive epidemiology, clinical features, treatments, and outcomes. The presence of isocitrate dehydrogenase gene mutation 1 (IDH1) has become one of the most critical biomarkers for molecular classification and prognosis in adult diffuse gliomas. About 65–90% of patients with adult diffuse gliomas have seizures as their initial symptoms. AIM: The objective of this study was to determine the association between IDH1 mutations in adult diffuse gliomas with an incidence of symptomatic epilepsy. METHODS: The study was conducted as an observational, cross-sectional, and prospective clinically controlled study at the Clinic of Neurosurgery of the Clinical Center of the University of Sarajevo. The research included a total of 100 patients treated at the Clinic of Neurosurgery, with pathohistological confirmation of glioma Grades II–IV who were stratified by groups according to tumor grade. Data were collected on tumor localization and grade, the presence of IDH mutations, and the presence of epileptic seizures as the first symptom of the glioma. RESULTS: Out of a total of 100 patients, 39 had IDH 1 mutations, while 61 patients were without them: Of these, diffuse astrocytoma Grade II 30 cases (30%), Grade III 5 (5%), and Grade IV 7 (7%), and the number of patients with glioblastoma was 58 (58%). In the group of patients with IDH 1 mutations, epileptic seizures were present in 87.2% compared to the group of patients without IDH 1 mutations (wild type) in which epileptic seizures were present in 16.4% of cases. Statistical analysis showed that the positive mutated IDH-type carries an almost 70% increase in the likelihood of epileptic seizures (χ2 = 8.378; p = 0.0001). If we separate the group of diffuse astrocytomas in the IDH 1-positive subgroup, 34 patients (85.81%) had epileptic seizures, while in the IDH 1-negative subgroup, there were no patients with epileptic seizures, which carries a statistically significant difference in frequency in favor of IDH 1-positive tumors (p ≤ 0.001). CONCLUSION: There is a clear connection between the presence of IDH1 mutations and the occurrence of epileptic seizures in the clinical picture of patients with diffuse adult glioma.